SEJARAH PERKEMBANGAN TEORI MANAJEMEN STRATEGI - Musfirah, Musfirah; Suban , Alwan (Cendikia: Jurnal Pendidikan dan Pengajaran, 2025)
This article reviews the history and development of strategic management theory from the Industrial Revolution to the current digital era. The evolution of this theory reflects a response to the dynamics of an increasingly complex and uncertain business environment. Using a descriptive qualitative approach and literature study, this study traces the transformation of the strategic management paradigm from an industrial structure and resource-based approach to contemporary approaches such as digital, platform, and goal-based strategies. In addition, this article also discusses the application of strategic management in the field of education in Indonesia, which has undergone significant transformation since the enactment of the National Education System Law in 2003. The results of the study show that strategic management has developed adaptively and dynamically, and has become an important instrument in increasing organizational competitiveness, both in the business and education sectors.